Ultrasound cyclo-plasty for moderate glaucoma: Eighteen-month results from a prospective study - Wang, Rui-Xue; Li, Ning; Chen, Xiao-Ya (Frontiers in Medicine, 2022)
Purpose: To evaluate the long-term clinical efficacy and molecular effects of ultrasound cyclo-plasty (UCP) for the treatment of moderate glaucoma. Methods: An 18-month clinical study was conducted among 32 patients with moderate glaucoma. The primary outcome was surgical success, defined as a reduction in intraocular pressure (IOP) of greater than or equal to 20% from the baseline and an IOP value of greater than 5 mmHg at the last follow-up. The secondary outcomes were related to the quality of life, complications, and mean IOP value at each follow-up. In the animal experiment, 20 New Zealand rabbits were used to establish a high-IOP model and implement UCP. The distribution of aquaporin 4 (AQP4) in the ciliary body and the tissue changes under electron microscopy were observed after surgery. Results: The mean patient IOP decreased from 34.9 ± 4.9 mmHg before surgery to 23.5 ± 5.2 mmHg at 18 months after UCP. No vision loss occurred in any patient. Some patients had postoperative complications, but the symptoms were mild and disappeared within 3 months after the surgery. Most patients had good postoperative quality of life. Histology showed that AQP4 remained in the ciliary muscle after UCP, and only the bilayered epithelial cells showed coagulative necrosis. Furthermore, electron microscopic observation revealed the destruction of ciliary process cells covered by ultrasound after UCP. Conclusion: UCP is associated with mild postoperative reactions and the mild treatment of ciliary tissue and is a safe and effective method for reducing IOP in moderate glaucoma. Keywords: glaucoma, ultrasound cyclo-plasty, intraocular pressure, ciliary body